Ansiaux, Traite D'Economie Politique - Mussey, H. R.; Ansiaux, Par Maurice (Quarterly Journal of Economics, 1926)
Journal Article Ansiaux, Traité D'Économie Politique Get access H. R. Mussey H. R. Mussey Wellesley College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 41, Issue 1, November 1926, Pages 163–167, https://doi.org/10.2307/1885557 Published: 01 November 1926